Getting Started With Electronic Music: An Open Course in Music Technology - Robert Willey (Journal of the Association for Technology in Music Instruction, 2021)
The curriculum for a music technology course is presented that is divided into four areas: digital audio sound manipulation, MIDI arranging and sequencing, online notation, and music videos. The course material is open to the public online and the skills that are developed while working through it can be of use to most music majors and to many of their professors in their work making music and teaching. The class is activity-based and taught in a flipped classroom with minimal lecturing. Students study the online material and come to class prepared to work through the tutorials during supervised lab sessions. The course content is available in an open online environment that anyone can access and is divided into modules so that parts of the course can be accessed and adapted individually. Students build online portfolios that can be reviewed by colleagues and explored by the general public instead of turning in assignments to the teacher. NASM expects graduates with degrees in music to have developed a number of basic skills, including composition/improvisation: “Students must acquire a rudimentary capacity to create original or derivative music. It is the prerogative of each institution to develop specific requirements regarding written, electronic, or improvisatory forms and methods.” One way to develop this competency could be through independent study, with students working on some or all of the material presented here and then submitting portfolios before graduation. This material can also be explored after graduating and used by the general public at any time.
Keywords: digital audio; sound manipulation; MIDI; sequencing; notation; video